PENDIDIKAN ISLAM RAMAH LINGKUNGAN PENERAPAN P5RA DALAM KURIKULUM MERDEKA DI MADRASAH TSANAWIYAH NURUL FALAH TANJUNG BARU - Zahara; Qonita; Yuberti; Abd. Rahman Hamid; Baharudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The increasingly worrying global environmental crisis is not only the responsibility of experts or activists, but also part of the responsibility of the world of education, including Islamic Education. Islamic education plays an important role in forming a generation that is not only religious. This study aims to examine the implementation of environmentally friendly Islamic education through the Pancasila Rahmatan lil 'Alamin Student Profile Strengthening Project (P5RA) at Madrasah Tsanawiyah Nurul Falah Tanjung Baru. The main focus of the activities includes waste management, greening through tree planting, and reusing used waste, which are combined with Islamic values such as responsibility, mutual cooperation, and amanah as a manifestation of the role of humans as khalifah fī al-ardh. This study uses a qualitative method with a case study approach, while data is obtained through interview, observation, and documentation techniques, then analyzed thematically and descriptively. The results of the study indicate that the implementation of P5RA makes a significant contribution to strengthening students' character, especially in terms of ecological awareness, discipline, and social empathy. The project-based learning model developed by teachers has been proven to encourage the growth of responsibility and spiritual awareness of the environment as part of worship to Allah SWT and this finding implies that the integration of Islamic values and environmental education in the madrasah curriculum creates contextual and sustainable learning.